2020
DOI: 10.1097/rct.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of PET(CT) in Patients With Neuroblastoma: A Meta-Analysis and Systematic Review

Abstract: Objective The objective of this study was to evaluate the overall diagnostic value of PET(CT) in patients with neuroblastoma (NB) based on qualified studies. Methods PubMed, Cochrane, and Embase database were searched by the index words to identify the qualified studies, and relevant literature sources were also searched. The latest research was performed in April 2019. Heterogeneity of the included studies was tested, which was used to select proper ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Our results were significantly different from the findings of Li and colleagues [9]. eir global sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and DOR were 17% (95% CI, 9%-30%), 78% (95% CI, 61%-89%), 0.80 (95% CI, 0.29-2.20), 1.05 (95% CI, 0.82-1.35), and 0.966 (95% CI, 0.254-3.671), respectively; the AUC was 0.32 (95% CI, 0.28-0.36).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results were significantly different from the findings of Li and colleagues [9]. eir global sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and DOR were 17% (95% CI, 9%-30%), 78% (95% CI, 61%-89%), 0.80 (95% CI, 0.29-2.20), 1.05 (95% CI, 0.82-1.35), and 0.966 (95% CI, 0.254-3.671), respectively; the AUC was 0.32 (95% CI, 0.28-0.36).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous meta-analysis suggested that 18 F-FDG PET had a higher sensitivity but lower specificity than MIBG scintigraphy in NB lesion detection [8]. Another recent meta-analysis reported a 17% pooled sensitivity of positron emission tomography (computed tomography) (PET(CT)) for the detection of bone marrow in pediatric NB in their subgroup analysis, which was significantly lower than several studies [9][10][11][12][13][14][15][16]. Superiorities of PET are high 18 F-FDG avidity of the bone marrow and imaging of the entire marrow [17].…”
Section: Introductionmentioning
confidence: 91%
“…First, while in 17 of 18 patients of our study cohort the target volume was defined by the extension of the MIBG-active lesion at the time of RT, previous studies defined the target volume as the volume visible on cross-sectional studies either at initial staging or after induction chemotherapy. Due to these diverging approaches resulting in different target volumes, the comparison of data remains challenging [18][19][20]. There were no general recommendations for the irradiation of metastases within NB 97 and NB 2004 and the indication for RT to metastatic lesions was based on individual decisions, forming a risk for selection bias [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma may occur in any part of the sympathetic nervous system. [ 3 ] However, Neuroblastoma most often occurs in the posterior abdominal cavity, especially in the adrenal glands. The statistics from the Taiwan Children's Cancer Foundation show about 30–40 new cases in Taiwan every year.…”
Section: Discussionmentioning
confidence: 99%